On-farm performance evaluation of Maale goats under agro-pastoral management in Southwest Ethiopia - Girma, Mekete; Nahom, Fikre; Getaneh, Demerew; Seid, Anwar (International Journal of Agricultural Research, Innovation and Technology, 2023)
This study was conducted in Maale district Southwest Ethiopia with the objective of evaluating the productive and reproductive performance of Maale goats under agro-pastoral management conditions. Thirty households that have flocks numbers of more than ten were purposely selected and monitored from July 2018 to July 2019. Growth data of birth weight, three month, six month, nine month and yearly weight; birth type and parity were collected. The data were analyzed using the General Linear Model (GLM) procedure of SPSS (21). The overall mean birth weight of the kids was 2.57±0.05 kg (males 2.68±0.07 and females 2.47±0.07 kg). The weaning and six months weight of kids was significantly different (p<0.05) between sexes of kids with 7.66±0.25 and 6.90±0.23 kg for male and female kids, respectively. The average body weight of males and females for six months; nine months and yearly were 11.57±0.30, 10.42±0.28; 15.42±0.27, 14.69±0.25 and 19.03±0.28, 18.43±0.25 kg, respectively. The birth type showed a significant (p<0.05) difference in birth weight. The result further indicated that the weaning weight of single and twin kids was highly significant (p< 0.001) and recorded as 7.66±0.25 and 6.90±0.23 kg, respectively. The overall pre-weaning average daily gain was 51.64±1.89 g day-1 (54.47±2.81 male and 48.93±2.53 g day-1 female). The birth type was significantly (p=0.01) different in pre-weaning growth rate and recorded 57.24±1.63 and 45.24±3.59 g day-1 for single and twin kids, respectively. Twins had higher post-weaning average daily gain than single and recorded as 43.61±1.48 and 40.76 ±0.70 g day-1, respectively. It was concluded that, along with other management interventions, the reproduction and growth performance of Maale goats is reasonably good and suited for community-based breeding strategies and higher performance could be expected. Int. J. Agril. Res. Innov. Tech. 12(2): 7-13, December 2022